Reactive Matrices for Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry of Primary Amines. Issue 3 (June 2015) - Zaikin, Vladimir G.; Borisov, Roman S.; Polovkov, Nikolai Yu.; Slyundina, Mariya S.
Some aromatic carbonyl compounds [2, 4-dihydroxybenzaldehyde (2, 4-DHBA), 2, 5-dihydroxyacetophenone (DHAP), 2, 3, 5-trihydroxybenzaldehyde and 2, 4-dinitrobenzaldehyde] were examined as potential reactive matrices for the analysis of mono-, di-, and polyamines by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS). Although all the above compounds readily and quantitatively react with primary amines to form Schiff bases (the completeness of the reactions was proved by gas chromatography MS of derivatized aliphatic amines), only DHBA and DHAP provide efficient desorption/ionization under MALDI conditions. This means that two these aromatic carbonyl compounds can simultaneously exhibit properties of both derivatization agents and efficient matrices for MALDI-MS analysis. The use of such reactive matrices eliminates the need to perform additional derivatization experiments. With the aid of DHBA and DHAP, it was confirmed that each individual oligomer of polypropylene glycols and co-polyethylene/propylene glycols contained two terminal amino groups. To calculate the number of NH2 groups, mass increments of the introduced groups and a difference in the masses of cations attached to the initial and derivatized amines were used. The suggested approach, involving the application of the same reactive matrices, was applied to the determination of a number of NH2 groups in individual oligomers of branched polyethyleneimines (PEIs) by MALDI-MS. In this case, DHAP appeared to be the best reactive matrix. The dependence of the number of NH2 groups on the quantity of monomeric units and branching of each individual PEI oligomer is shown.